Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective. Issue 4 (4th July 2014) - Jones, Aisla C; Mead, Angela; Kaiser, Michel J; Austen, Melanie C V; Adrian, Alex W; Auchterlonie, Neil A; Black, Kenneth D; Blow, Lucy R; Bury, Charlotte; Brown, Janet H; Burnell, Gavin M; Connolly, Elaine; et al.
Abstract Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a 'task force' group of 36 'practitioners' and 12 'research scientists' who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by 'practitioners' or 'research scientists'. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.